RESENHA: GOLDSCHMIDT, NORA. "SHAGGY CROWNS: ENNIUS’ 'ANNALES' AND VIRGIL’S 'AENEID'" | REVIEW: GOLDSCHMIDT, NORA. "SHAGGY CROWNS: ENNIUS’ 'ANNALES' AND VIRGIL’S 'AENEID'" - Moura, Fernanda Messeder (Estudos Linguísticos e Literários, 2016)
Goldschmidt, Nora. Shaggy Crowns: Ennius’ Annales and Virgil’s Aeneid. Oxford; New York: Oxford University Press, 2013. 258pp. ISBN 9780199681297.